THE EFFECTIVENESS OF FISHBOWL TECHNIQUE TOWARDS STUDENTSâ SELF EFFICACY IN SPEAKING - Effendi, Azwan (IKIP Mataram, 2017)
This study is generally attempted to find out whether or notÂ of Fishbowl techniqueÂ effective towards studentsâ self efficacy in speaking for second grade students of SMPNÂ 1 Sikur academic year 2017/2018. method of this research was applied is experimental research (quantitative approach). The population of this research was of second grade students at SMPN 1 Sikur. which consistes of eight classes. the samples, were VIII A as experimental class, and VIII C as control class. They were chosen by using cluster random sampling technique with lottery. Experimental class was treated by using fishbowl technique, and control class was treated by using role play. The technique which was used to analysis the data was test formula. From the research data found out that the studentsâ t-test score (1,73) and t-table (1,667) from (df) was 64. Based on the result of the study, and the correlation between self-efficacy and speaking was r-test (2,70) > r-table (0,320). It can be concluded that the use of fishbowl technique has positive effect toward studentsâ self-efficacy in speaking and has correlation both of them at the second grade students SMPN 1 Sikur academic year 2017/2018.